Investigating the Expression Level of Mir-361 in Patients with Breast Cancer - S Igder; M Sharifat; S Iranparast; A Tallaeizade; M Ghasemi Deh Cheshmeh; M Rashno; A Ghadiri; A Amari; A Saeedi Boroujeni; A Khodadadi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: MicroRNAs are a new group of small regulatory RNAs, some of which are expressed differently in normal and tumor tissue. The aim of this study was to investigate the expression of miR-361 in breast tumor tissue of patients with breast cancer. Methods: In this cross-sectional study conducted from January 2012 to February 2021 in Ahvaz Jundishapur University of Medical Sciences, 30 breast cancer samples were grouped based on clinicopathological characteristics including tumor size, cancer stage, lymphovascular invasion, molecular subtypes, etc. Then, expression analysis was performed using Real-Time PCR, and the expression level of miR-361 gene in tumor and healthy samples and its relationship with clinicopathological characteristics were investigated. Findings: The expression of miR-361 was significantly reduced by 1.5-fold in cancerous tissue compared to adjacent normal tissue, and this reduction in expression was only significantly associated with triple-negative breast cancer (TNBC) (p=0.02). The expression level was also significantly reduced in tumors larger than or equal to 3 cm (0.93±0.79) compared to smaller tumors (0.17±0.18) (p=0.031). The ratio of reduction in miR-361 expression in stages (I & II) compared to (III & IV) was 0.29±0.44 and 0.91±1.31, respectively (p=0.308). On the other hand, the ratio of decreased expression in the two groups with and without lymphovascular invasion was determined to be 0.39±0.33 (p=0.682) and 0.15±0.16 (p=0.547), respectively, but this difference was not statistically significant. The AUC for miR-361 for breast cancer diagnosis was 0.71 (p=0.031). Conclusion: Based on the results of this study, and considering the role of miR-361 in breast cancer progression and its relationship with clinicopathological factors, it may be possible to introduce it as a new diagnostic marker in breast cancer.